Interdomain path computation challenges and solutions for label switched networks. - Aslam, Faisal; Uzmi, Zartash Afzal; Farrel, Adrian
For label switched networks, such as MPLS and GMPLS, most existing traffic engineering solutions work in a single routing domain. These solutions do not work when a route from the ingress node to the egress node leaves the routing area or autonomous system of the ingress node. In such cases, the path computation problem becomes complicated because of the unavailability of the complete routing information throughout the network. This is because service providers usually choose not to leak routing information beyond the routing area or AS for scalability constraints and confidentiality concerns. This article serves two purposes. First, it provides a description of the existing and ongoing work in interdomain TE within the IETF. This information is currently found in various Internet drafts and has not yet been collectively presented in a single document. To this end, a summary of both existing path computation architectures - PCE-based and per-domain - is provided. Second, it compares two per-domain path computation schemes in terms of the total number of LSPs successfully placed and average number of domains crossed, without assuming availability of complete topology information. We notice that the two per-domain path computation schemes, proposed in [1, 2], have comparable path computation complexities and setup latencies.
Keywords: IETF; Internet; Autonomous system; Interdomain path computation challenge; Label switched network; Network traffic engineering; Single routing domain; Traffic engineering solutions